Digital Technology Adoption and its relationship with Human Resource Management Practices in Higher Education Institutions of Balochistan - Dr. Zahida Abdullah (Social Science Review Archives, 2025)
This study aims to explore the adoption of digital technologies and its correlation with HRM practices in HEIs of Balochistan, Pakistan. The use of digital technology, in the modern context of academic life, has become more and more significant enhancing HR related processes, especially recruitment and selection, training and development. The study used a quantitative research design and the sample consisted of 400 respondents comprising of academic faculty and administrative staff of Sardar Bahadur Khan Women University (SBKWU), Balochistan University of Information Technology, Engineering and Management Sciences (BUITEMS) and the University of Balochistan (UoB). Data were collected by a structured questionnaire and analyzed with SPSS. The results showed that the level of the digital technology adoption of respondents was moderate. Digital recruitment was generally well received, especially in terms of speeding up the recruitment process, better candidate records management and the ability to ensure a fair candidate selection. Likewise, digital tools were identified to facilitate training and development including through professional development, job performance, and ongoing learning. The results of the correlation indicated that there were strong positive and statistically significant relationships between digital technology adoption and recruitment and selection, r (398) = .680, p < .001; digital technology adoption and training and development, r (398) = .720, p < .001; and between recruitment and selection and training and development, r (398) = .700, p < .001. The results suggest a strong positive relationship between the use of digital technology and the HRM practices in HEIs. The study suggests that there is a need to increase the institutional digital infrastructure, thus providing better access to digital HR platforms, as well as to conduct continuous training to increase digital tools efficiency in HRM processes.